Duration of treatment effect should be considered in the design and interpretation of clinical trials: results of a discrete choice experiment - Copsey, B; Buchanan, J; Fitzpatrick, R; Lamb, SE; Dutton, SJ; Cook, JA (SAGE Publications, 2019)
Objective This study examined whether the duration of treatment effect should be considered in a benefit-risk assessment, using a case study of osteoarthritis medications. Study design and setting A discrete choice experiment was completed by 300 residents of the United Kingdom with hip and/or knee osteoarthritis. In 16 choice tasks, participants selected their preferred option from 2 medications. Medications were described in terms of the effect on pain, stiffness, and function, duration of treatment effect, and risk of heart attack and stomach ulcer bleeding. Analysis used mixed-effects logistic regression. Results Pain, severity and duration of treatment effect had the greatest influence on medication preferences, whereas stiffness did not significantly affect medication choice. Participants were willing to accept an increase in the risk of heart attack of 2.6% (95% CI: 2.0% to 3.2%) to increase duration of the treatment effect from one month to 12 months. Reducing pain from moderate to mild was valued the same as increasing duration of effect from one month to three months; both were seen as equivalent to an absolute reduction of 1.2% in the risk of heart attack in the next year. Subgroup analysis suggested disease severity influenced patient preferences. Conclusions Along with treatment benefits and risks, the results suggest that duration of treatment effect is an important factor in the medication choices of people with osteoarthritis. This could have implications for the design and interpretation of clinical trials, for example, incorporating longer-term surveillance of trials participants and account for duration of treatment effect in risk-benefit assessments. Future research is needed to assess whether these findings are generalisable to other samples, disease areas and levels of duration of effect.